Rochinia confusa, a junior synonym of R. umbonata (Crustacea: Brachyura: Epialtidae) as revealed by ontogenetic changes - Tavares, Marcos (2016)
The carapace and chelipeds ornamentation of the deep-water spider crab Rochinia umbonata (Stimpson, 1871), from the Western Atlantic undergo very dramatic ontogenetic changes. Since the also deep-water spider crab Rochinia confusa Tavares, 1991 is differentiated from R. umbonata mostly on the basis of these characters, R. confusa is regarded herein as an ontogenetic stage and, therefore, a junior subjective synonym of R. umbonata.